Pig Iron and Scrap Prices during Business Cycles - Blackett, O. W. (The Review of Economics and Statistics, 1923)
THE following paper presents an analysis of the relative price movements of the two most important raw materials used the manufacture of iron and steel products. The place of pig iron in the industry is well known. The place of scrap or recovered metal is little understood outside the trade itself. The market for scrap is nearly coextensive with that for pig. Since scrap is naturally of a very high iron content, it is a strong competitor of pig iron the large producing centers and a partial or complete substitute on the Atlantic seaboard and the west. Indeed some sections of the country are able to maintain a considerable industry without any resort to pig iron a,s a raw material. There has grown up a large industry connected with the collection and preparation of scrap, some firms having a capital of over a million dollars and an annual business of over fifty millions. Of the total scrap products estimated to be worth about four hundred millions annually about one half is handled by middlemen, the other half passes directly from the producing to the consuming plant or is consumed the plant where it originates. Since it is usual for wholesalers or brokers not only to finance the small country collector but to extend credit to the consuming mills, any price change which may occur is a matter of importance for their credit relations. The real significance of the fluctuations of scrap and iron prices is, however, best understood when it is realized that the proportion of scrap and pig used iron and steel works depends quite as much on their relative prices as on the technique of the industry. A typical charge for the basic open-hearth furnace is six tons iron scrap, thirty-two tons steel scrap, and thirty-six tons pig iron; but the charge may vary within very wide limits, sometimes pig and ore, sometimes pig and scrap, or even all scrap. The fundamental limitation on the use of scrap, namely some slight uncertainty as to its analysis, is not a dominant consideration so flexible a process as the open-hearth. A change the price of pig iron disproportionate to the change scrap may, therefore, make a considerable difference the proportions used. In foundry practice the same alternative is found, although work of the highest quality there is not great latitude for varying the materials. Rolling mills also make extensive use of scrap for rerolling or for piling, heating to a welding heat, and rolling into bars. Only the production of crucible steel, malleable castings and a few special products is there a real lack of flexibility the uses to which scrap may be put. Therefore, a large part of the iron and steel industry watches with care not only the cyclical changes the price of its raw materials but also the differences which from time to time appear between them.